The Effect of Moringa Leaf Fortification on Improving the Nutritional Status of Stunting Toddlers in Coastal Areas - Ayu Dewi Nastiti; R.A. Helda Puspitasari; Dwining Handayani; Ferdi Rahmad Irwansyah (Health and Technology Journal (HTechJ), 2025)
Stunting is still a serious problem in many developing countries, including Indonesia. The government has taken various steps to address this condition, one of which is through the Supplementary Feeding Program (PMT). Baby food products containing moringa leaves are considered to be able to help in dealing with stunting. This study aims to evaluate the effectiveness of implementing a healthy diet with moringa leaf fortification in handling stunted toddlers. The research method used was a quasi-experiment involving 50 toddlers divided into two groups: 25 in the treatment group and 25 in the control group. The study showed increased height in toddlers given moringa leaf-based food through fortification. On average, toddler height increased by 2.9 cm after the intervention. The results of the paired sample t-test statistical test showed a significance value of 0.003 (<0.05), indicating that moringa leaf fortification effectively improved the nutritional status of stunted toddlers. These findings suggest that moringa fortification could be a viable, sustainable approach to combat stunting in resource-limited settings. However, further research through randomized controlled trials and longitudinal studies is recommended to validate these outcomes and explore broader applications in public health nutrition programs.